EFEKTIVITAS PENANGGULANGAN VIRUS HIV/AIDS KABUPATEN MAMUJU - Mansyur, Nur Asia; Madani, Muhlis; Abdi, Abdi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This study aims to determine the effectiveness of HIV/AIDS prevention at the Mamuju District Health Office. The research method used was qualitative. Data collection techniques in this study were interviews, observation and documentation. The results of this study showed that the effectiveness of HIV/AIDS prevention at the Mamuju District Health Office was running well and effectively. HIV/AIDS sufferers through administration of ARV drugs. (2) the integration that was carried out was socialization which was replaced with VCT activities. The Mamuju Regency Health Office with the Puskesmas and NGOs to carry out VCT activities for hotels and night entertainment (3) adaptations carried out by the Mamuju District Health Office and the Puskesmas and NGOs, namely carrying out programs such as administering ARV drugs, home visits,